Utilization of gasification slag and petrochemical incineration fly ash for glass ceramic production - Hao, Zhenyu; Zhang, Hai; Tang, Xiaoli; Sui, Lihua; Li, Yanan; Zhang, Shucai (Frontiers in Chemistry, 2023)
This study investigated glass ceramics produced using coal gasification slag (CGS) and petrochemical incineration fly ash (PIFA) to immobilize hazardous heavy metals such as Cr and As. However, the crystallization kinetics and stabilization behavior mechanism of different heavy metals in the petrochemical incineration fly ash-derived glass-ceramics remains unclear. And X-ray diffraction, differential scanning calorimetry, scanning electron microscopy, and inductively coupled plasma mass spectrometry were used to characterize glass and crystalline products. In this paper, we reported the crystallization kinetics and chemical leaching characteristics of the glass ceramic. A low crystallization activation energy of 121.49 kJ/mol was achieved from crystallization peak of several different heating rates around 850°C, implying that it is easier to produce the glass ceramics at that temperature. The Avrami parameter of the former crystallization was determined to be 1.23 ± .12, which indicated two-dimensional crystal growth with heterogeneous nucleation. The toxicity characteristic leaching procedure results indicated that the heavy metals were well solidified, and that the leaching concentration was significantly lower than the limit specified by governmental agencies. The potentially toxic element index of the parent glass and the two glass ceramics were 11.7, 5.8, and 3.6, respectively. Therefore, the conversion of hazardous petrochemical incineration fly ash and other solid waste into environmentally friendly glass ceramics shows considerable potential and reliability.